Hal Hartley - Berrettini, Mark L., 1972- (Contemporary film directors., 2011)
"Since the late 1980s, Hal Hartley has challenged standards of realist narrative cinema with daring narrative constructions, character development, and the creation of an unconventional visual world. In this pioneering critical overview of his work and its cultural-historical context, Mark L. Berrettini discusses seven of Harley's feature films ... Drawing on journalism, theories of representation, narrative and genre, and cinema history, Berrettini discusses the absurdist-comedic representation of serious themes in Harley's films: impossible love, coincidence and human relations, extreme isolation, and the restrictions posed by gender norms. He notes how these themes reappear withing framing narratives that shift from the seemingly mundane in Harley's earliest works to the vibrantly creative and fantastic in his later films. Employing close analysis and theories related to cinematic narrative and realism, the book considers aspects of American independent cinema and postwar European cinema, antirealism, and minimalism. The volume concludes with a pair of in-depth interviews with the director from two distinct points in his career."--Back cover.